Essays in applied microeconomics : smart networks and behaviour of households and firms - McCoy, Daire (Trinity College (Dublin, Ireland). Department of Economics, 2016)
This dissertation explores a number of aspects related to the roll-out of network infrastructure. The focus is on the integration of electricity networks and ICT, and the interaction of these technologies with the behaviour of households and firms. This work is empirical in nature and employs simulation and econometric modelling techniques, in order to examine a broad range of questions related to this. There is a particular focus on the spatial distribution of effects, given the heterogeneity that exists in both network infrastructure provision, and household and firm locations across geographies. Chapter 1 provides the introduction, along with a general background to this research, and then outlines the specific research questions that are explored in this dissertation. Chapter 2 examines in detail the role in which improved information on electricity usage through ICT can have on household investment decisions related to energy efficiency. This paper uses data from a nationally representative smart-metering trial, in which smart electric meters were placed in Irish dwellings in an effort to examine the potential for improved information and time-of-use pricing to encourage reduction of electricity usage, and time-shifting of demand. This research exploits before and after survey questions related to the stock and ow of energy efficiency technologies within the home to demonstrate a case in which improved information can help reduce consumption, but can also negatively impact the adoption of energy efficient technologies. Binary and count regression models are employed in this analysis. A paper based on this research and co-authored with my supervisor, Dr. Seán Lyons has recently been accepted for publication in the journal Energy Efficiency. Chapter 3 examines the potential of future electric vehicle adoption patterns to concentrate excess demand at certain nodes of electricity distribution networks. This analysis is applied to Ireland and demonstrates also how individual level survey data, from a smart-metering trial, can be combined with spatial census aggregate data in an agent-based model to simulate technology adoption profiles for geographic areas within which diverse ranges of households reside. Results show the overall diffusion level in the population may be determined by the order of adoption. We also find that significant clusters may form in certain geographic areas, even if overall adoption levels remain low. Ultimately, this work emphasises the uneven spatial nature of technology adoption and the potential impact of this on electricity distribution networks. A paper based on this chapter, co-authored with Dr. Seán Lyons has appeared in the journal Energy Research and Social Science, Volume 3 (July 2014). Chapter 4 examines the impact of broadband infrastructure, electricity networks, other infrastructure including motorways, airports and railways and a range of other factors such as human capital and third level institutes on new business establishments. This chapter is a slight departure in that the emphasis shifts from households to firms; however, there is a degree of symmetry between this work and Chapter 3. While Chapter 3 examined the spatial location of households and the impact this may have on electricity networks, this chapter looks at the spatial configuration of network infrastructure and how this affects the location of firms. The results show that increased numbers of foreign firms and high-tech firms emerge in areas where broadband is available and they also prefer better broadband. Importantly, human capital and proximity to a third level institution are also important determinants of new firm establishments, including low-tech indigenous _rms. Complementarities also exist between human capital and ICT, in that an area's ability to attract new firms with improved ICT depends on its level of human capital. The overall aim of this chapter is to examine how the provision of infrastructure and other factors affect the spatial distribution of economic activity. This is relevant in cases where publicly funded infrastructure projects are initiated in order to disperse economic activity in a more geographically balanced fashion. A paper based on this chapter, co-authored with Dr. Seán Lyons and Dr. Edgar Morgenroth of the ESRI, Dr. Donal Palcic of the University of Limerick and Ms Leonie Allen of the Commission for Communications Regulation (ComReg), has been submitted to the Journal of Economic Geography. Chapter 5 concludes the dissertation and links the research back to the overall theme of the roll-out of ICT and its integration with electricity networks. Limitations of the research are highlighted and potentially fruitful avenues of future research are discussed.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin